The Role of Parents in Shaping the Discipline and Achievement of Santri: A Case Study at Muharrikunnajaah Islamic Education Center - Arman Maulana Ridho; Mahasri Shobahiya; Marsekal Rahman Hakiem (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This research investigates how parental roles contribute to shaping discipline and achievement of santri (Islamic boarding school students) within a pesantren environment. Using a qualitative case study approach, data were collected through in-depth interviews with homeroom teachers, musyrif (supervisors), 30 parents, and 30 santri at Muharrikunnajaah Islamic Education Center; direct observation; and documentation. Participants were selected via purposive sampling from diverse regional, educational, and socioeconomic backgrounds. Data analysis employed an interactive model consisting of data collection, reduction, presentation, and conclusion drawing, with source triangulation ensuring validity. The findings reveal that parental roles significantly impact santri discipline and achievement. The pesantren facilitates this through regular monthly telephone calls, weekly letters containing progress reports and advice, and and food delivery twice a month. Of 30 santri studied, 15 who received authentic advice from parents, characterized by encouragement for worship discipline, learning motivation, and positive role modelling, demonstrated high discipline levels and superior achievement, with 15 ranking in top five of their classes and 5 winning academic and non-academic competitions. Conversely, 15 santri receiving inconsistent advice showed different outcomes: 6 received disciplinary warnings for violations, while others maintained discipline but achieved lower academic grades (70-80 versus 85-95). This research concludes that parental roles, facilitated by pesantren, are crucial in forming disciplined and achieving santri. The study contributes theoretically to understanding Islamic value transmission through families as harmonious ta'dib (Islamic education) and practically by encouraging family-pesantren collaboration to prevent moral degradation and support contemporary Islamic civilization advancement.